Horizontal Cells, the Odd Ones Out in the Retina, Give Insights into Development and Disease - Boije, Henrik; Shirazi Fard, Shahrzad; Edqvist, Per-Henrik; Hallböök, Finn (Frontiers in Neuroanatomy, 2016)
Thorough investigation of a neuronal population can help reveal key aspects regarding the nervous system and its development. The retinal horizontal cells have several extraordinary features making them particularly interesting for addressing questions regarding fate assignment and subtype specification. In this review we discuss and summarize data concerning the formation and diversity of horizontal cells, how morphology is correlated to molecular markers, and how fate assignment separates the horizontal lineage from the lineages of other retinal cell types. We discuss the novel and unique final cell cycle of horizontal cell progenitors and how it may relate to the formation of retinoblastoma.